Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1468-3083.2011.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical niacin cream‐assisted 595‐nm pulsed‐dye laser treatment for facial flushing: retrospective analysis of 25 Korean patients

Abstract: We suggest that 595-nm pulsed-dye laser treatment after provocation of flushing by topical niacin cream may provide a new treatment algorithm for facial flushing in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Application of the 401 ± 5 nm blue LED at a mean irradiance of 0.000773 W/cm2 for 30 min, with 1.3914 j/ cm2 total exposure, does not lead to adverse events or changes in the properties of the healthy vaginal mucosa. (10) Additionally, the 405 nm blue LED has been identified as an effective alternative for managing candidal vulvovaginitis. (11,12) Recently, Wang et al reported the effectiveness of 405-nm aBL in inactivating N. gonorrhea while preserving vaginal epithelial cells.…”
Section: Exploring the Efficacy And Clinician Experience Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of the 401 ± 5 nm blue LED at a mean irradiance of 0.000773 W/cm2 for 30 min, with 1.3914 j/ cm2 total exposure, does not lead to adverse events or changes in the properties of the healthy vaginal mucosa. (10) Additionally, the 405 nm blue LED has been identified as an effective alternative for managing candidal vulvovaginitis. (11,12) Recently, Wang et al reported the effectiveness of 405-nm aBL in inactivating N. gonorrhea while preserving vaginal epithelial cells.…”
Section: Exploring the Efficacy And Clinician Experience Withmentioning
confidence: 99%
“…Topical and oral systemic pharmacologic agents have been shown to reduce hyperhidrosis, but often have serious side effects and may not be as effective in more severe cases (7)(8)(9). Botulinum toxin A applied to the axillae has been shown in many studies to be a safe and highly effective treatment option for the condition but must be repeated six to 9 months on average for consistent results (10)(11)(12). Surgical options, such as removal of sweat glands through suction-curettage (13), or cutting the nerves that the body uses to send signals to the sweat glands, known as sympathectomy, can be highly effective in reducing sweat, but typically carry more risk, involve longer periods of recovery, and may lead to compensatory sweating in some cases (14,15).…”
Section: Comparison Of Short Medium and Long-term Efficacy And Number...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hot flashes last for an average of 7.4 years, but its duration may vary depending on race or ethnic group [1]. Chronic repetitive and strong facial flushing may cause a loss of vascular tone, resulting in a permanent background of redness and telangiectasias, creating psychological distress [3]. Nonpharmacologic therapies for menopausal symptoms are generally less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Flushing is a visible symptom of increased cutaneous blood flow, and is restricted to areas with more visible superficial cutaneous vasculature and higher erythrocyte counts [3]. Due to the brief and episodic nature of flushing, it is possible that patients may not present with erythema during their laser treatment sessions, making it difficult to set targeted treatment areas [3,[13][14][15].…”
mentioning
confidence: 99%